1998
DOI: 10.1104/pp.116.4.1315
|View full text |Cite
|
Sign up to set email alerts
|

Cyst(e)ine Is the Transport Metabolite of Assimilated Sulfur from Bundle-Sheath to Mesophyll Cells in Maize Leaves1

Abstract: The intercellular distribution of the enzymes and metabolites of assimilatory sulfate reduction and glutathione synthesis was analyzed in maize (Zea mays L. cv LG 9) leaves. Mesophyll cells and strands of bundle-sheath cells from second leaves of 11-d-old maize seedlings were obtained by two different mechanical-isolation methods. Cross-contamination of cell preparations was determined using ribulose bisphosphate carboxylase (EC 4.1.1.39) and nitrate reductase (EC 1.6.6.1) as marker enzymes for bundle-sheath a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 47 publications
(6 reference statements)
6
55
1
Order By: Relevance
“…Its accumulation was increased in the BS chloroplasts (twofold), which was consistent with previous localization of primary sulfur assimilation in the BS cells by activity measurements (Burgener et al, 1998). Cystein was proposed to be the transport factor for sulfur between M and BS cells (Burgener et al, 1998). A cystein synthase (TC235388 and TC235390) was slightly higher in the M chloroplast (1.6-fold), suggesting that secondary assimilation of H 2 S takes place in M chloroplasts.…”
Section: S-assimilationsupporting
confidence: 77%
See 1 more Smart Citation
“…Its accumulation was increased in the BS chloroplasts (twofold), which was consistent with previous localization of primary sulfur assimilation in the BS cells by activity measurements (Burgener et al, 1998). Cystein was proposed to be the transport factor for sulfur between M and BS cells (Burgener et al, 1998). A cystein synthase (TC235388 and TC235390) was slightly higher in the M chloroplast (1.6-fold), suggesting that secondary assimilation of H 2 S takes place in M chloroplasts.…”
Section: S-assimilationsupporting
confidence: 77%
“…Possibly this is due to the presence of different SOD homologs and different isolation procedures. Comparisons between the total maize leaf extracts and rapid M sap extractions showed that glutathione (Burgener et al, 1998), dehydroascorbate reductase, and GR were localized in the M, while ascorbate peroxidase was found in the total leaf extracts (Doulis et al, 1997). As GR mRNA was distributed in both compartments, a translational regulation mechanism of differential expression was proposed (Pastori et al, 2000).…”
Section: Proteins Involved In Detoxification Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…With regard to synthesis within the principal maize leaf photosynthetic tissues, i.e. the M and BS cells, a previous study using rapid tissue fractionation techniques showed that GSH-S activity was enriched in tissues other than the BS, though no data was reported for g-ECS (Burgener et al, 1998). Our results suggest that g-ECS and GSH-S proteins are found in both cell types, as well as in the epidermal cells (Fig.…”
Section: Although Global Leaf G-ecs Total Protein and Activity Are Nomentioning
confidence: 45%
“…In maize, our knowledge of the regulation of glutathione biosynthesis during the chilling response is limited by the lack of gene sequences for any C 4 or monocotyledonous species and by the absence of expression data for g-ECS and GSH-S during chilling. The regulation of glutathione synthesis in maize is further complicated by data that suggest that, whereas Cys synthesis occurs exclusively in the BS, GSH-S activity is located primarily in the M cells (Burgener et al, 1998). No data has yet appeared on g-ECS localization in maize leaves.…”
mentioning
confidence: 99%
“…The intracellular compartmentalization was determined based first on the MetaCrop database (Schreiber et al, 2012), literature sources (Friso et al, 2010;Chang et al, 2012), compartmentalization information in the MaizeCyc database, and finally the Plant Proteomics Database (Sun et al, 2009). An original set of intercellular and intracellular transporters was determined based on literature evidence (Alberte and Thornber, 1977;Leegood, 1985;Stitt and Heldt, 1985;Furbank et al, 1989;Weiner and Heldt, 1992;Doulis et al, 1997;Burgener et al, 1998;Taniguchi et al, 2004;Sowi nski et al, 2008;Friso et al, 2010). In the subsequent standardization step, the MetRxn knowledgebase (Kumar et al, 2012) as well as manual curation were used to standardize the description of metabolites and reactions such as fixing stoichiometric errors (i.e.…”
Section: Model Development and Curationmentioning
confidence: 99%